Theory into practice: Challenges and implications for information literacy teaching. (June 2020) - Schachter, Deborah
This article is informed by a mixed-methods research study into librarians' critical information literacy awareness and teaching practices in higher education institutions within British Columbia, Canada, and the literature related to critical pedagogical and literacy theory. I explore the perceived gap in librarian knowledge of theories that underpin their pedagogy, the value of learning about and applying theories to information literacy teaching, and strategies that can enable improved awareness and application of theory to librarians' practices in higher education.